Analysis Marketing Strategy Of Online Shop Business Catalogguee In Watansoppeng - Mastura, Mastura; Darwis, Muh; Rivai, Muh (Universitas Negeri Makassar, 2025)
Analysis of the Online Shop Catalogguee Competitive Strategy in Watansoppeng is one way to find out a good competitive strategy used in running a business. Problems that arise is how the application of competitive strategy and determinant factors in implementing competitive strategy. To achieve this goal, then used data collection techniques through observation, interviews, and documentation. The data is processed using a qualitative approach. This study took 10 (people) with representatives and fulfilled criteria in this study. The data source in this research is data primary using an interview guide. The results of this study show that the implementation of competitive strategy has several indicators, including through price, through brand image, through product design, through quality, and through service. The determinant factors in implementation of competitive strategy, namely supporting factors consisting of the quality of the product, the use of social media as a means of promotion, and the use of company operational standards. The constraints consist of producers of product raw materials, places, and competition factor. The interview technique was carried out in a manner structured with As for factors